Multidecadal accumulation of anthropogenic and remineralized dissolved inorganic carbon along the Extended Ellett Line in the northeast Atlantic Ocean. Issue 2 (20th February 2016) - Humphreys, Matthew P.; Griffiths, Alex M.; Achterberg, Eric P.; Holliday, N. Penny; Rérolle, Victoire M. C.; Menzel Barraqueta, Jan‐Lukas; Couldrey, Matthew P.; Oliver, Kevin I. C.; Hartman, Susan E.; Esposito, Mario; Boyce, Adrian J.
Abstract: Marine carbonate chemistry measurements have been carried out annually since 2009 during UK research cruises along the Extended Ellett Line (EEL), a hydrographic transect in the northeast Atlantic Ocean. The EEL intersects several water masses that are key to the global thermohaline circulation, and therefore the cruises sample a region in which it is critical to monitor secular physical and biogeochemical changes. We have combined results from these EEL cruises with existing quality‐controlled observational data syntheses to produce a hydrographic time series for the EEL from 1981 to 2013. This reveals multidecadal increases in dissolved inorganic carbon (DIC) throughout the water column, with a near‐surface maximum rate of 1.80 ± 0.45 µmol kg −1 yr −1 . Anthropogenic CO2 accumulation was assessed, using simultaneous changes in apparent oxygen utilization (AOU) and total alkalinity (TA) as proxies for the biogeochemical processes that influence DIC. The stable carbon isotope composition of DIC (δ 13 CDIC ) was also determined and used as an independent test of our method. We calculated a volume‐integrated anthropogenic CO2 accumulation rate of 2.8 ± 0.4 mg C m −3 yr −1 along the EEL, which is about double the global mean. The anthropogenic CO2 component accounts for only 31 ± 6% of the total DIC increase. The remainder is derived from increased organic matter remineralization, which we attribute to the lateral redistribution of water masses that accompanies subpolar gyre contraction. Output from a general circulation ecosystem model demonstrates that spatiotemporal heterogeneity in the observations has not significantly biased our multidecadal rate of change calculations and indicates that the EEL observations have been tracking distal changes in the surrounding North Atlantic and Nordic Seas. Key Points: In the NE Atlantic, DIC has increased at all depths in the period 1981‐2013 AOU, TA, and δ 13 CDIC show that approximately 31% of DIC increase is anthropogenic Model output confirms that rates of change determined from observations are robust